Experimental Study of Drying Fruits and Vegetables Using The Freeze Drying Method With The Aim of Maintaining The Nutrition and Effectiveness of Processed Products - Yusuf, Mirza; Nulhakim, Lukman; Prambandono, Bayu; Wisnujati, Andika; Yudhanto, Ferriawan (Universitas Muhammadiyah Yogyakarta, 2025)
The potential of natural resources in tropical countries is very diverse. one of them is the abundant agricultural products. but there are some obstacles in the post-harvest cycle and the continuous availability when the harvest season ends. various methods of preserving agricultural products have been tested from conventional methods to advanced technology. one of the technologies for preserving agricultural products is freeze drying. various innovations continue to be tested until they get consistent results with good energy efficiency. This method was originally started in the pharmaceutical industry. Various treatments and flexible adaptations make this method penetrate the food industry to maintain the quality of food products. In the food industry, freeze drying is suitable for food products such as meat, fruits, grains, and vegetables. The advantage of freeze drying is that the food products produced do not change shape, form, texture, taste, and nutrition even though they have gone through the drying process. Of the various characteristics of fruits and vegetables have their own properties that can be changed with the temperature parameters applied in the freeze dryer method.